The Direction of Islamic Religious Education in High Schools and Vocational Schools: Analysis of Government Policy in Government Regulation of The Republic of Indonesia Number 4 of 2022 - Prosmala Hadisaputra; Muhammad Thohri; Muh Zulkifli (PAEDAGOGIA, 2025)
Islamic education demands focused governmental attention through strategic policy-making, as it plays a vital role in shaping societal values and development. This issue is especially critical in countries with a religious foundation like Indonesia, where Islamic education serves as a key pillar in fostering moral integrity, spiritual growth, and cultural cohesion. This study investigates the trajectory of Islamic education in Senior High Schools (Sekolah Menengah Atas/SMA) and Vocational High Schools (Sekolah Menengah Kejuruan/SMK) as delineated in Government Regulation of the Republic of Indonesia Number 4 of 2022. The research is anchored in a fundamental inquiry: What is the direction of Islamic education in Senior High Schools and Vocational Schools from the perspective of Republic of Indonesia Government Regulation Number 4 of 2022? Employing a qualitative approach within a policy analysis framework, this study relies on primary data extracted from the aforementioned regulation. The findings reveal: (1) the orientation of Islamic education towards achieving Graduate Competency Standards in Senior High Schools and Vocational Schools; (2) the designation of Islamic Religious Education as a compulsory subject within the curriculum of Senior High Schools and Vocational Schools; (3) the establishment of Islamic Religious Education as a mandatory subject in Senior High Schools and Vocational Schools; and (4) the key priorities that must be addressed in the development of the Islamic Religious Education curriculum for Senior High Schools (SMA) and Vocational High Schools (SMK). This study contributes comprehensively to delineating the direction and implementation of Islamic education policies at the secondary education level in Indonesia.